Implementasi Model Problem Solving dalam Meningkatkan Keterampilan Siswa Berpikir Kritis - Hayuani, Hayuani; Hadijah , Siti; Firmansyah, Firmansyah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Learning methods have an important role in improving student learning outcomes. This study aims to analyse the effectiveness of the inquiry method in improving learning outcomes in Science at SMPN 2 Bagan Sinembah Raya. The inquiry method emphasises exploration, investigation and problem solving, allowing students to discover concepts independently as well as improving their understanding and critical thinking skills. This research used the Classroom Action Research (PTK) method with four main stages: planning, implementation, observation, and reflection. The research subjects were grade VIII students who had difficulty in understanding conventional science concepts. Data were collected through observation, learning outcome tests before and after the application of the inquiry method, as well as interviews with students and teachers. Data analysis was done descriptively comparative to see changes in learning outcomes and student engagement. The results showed that the inquiry method significantly improved students’ understanding and participation in science learning. Students become more active, motivated, and able to develop critical thinking skills. However, challenges in implementing this method include teacher readiness, availability of laboratory equipment, and the need for intensive guidance for students who are not used to exploration-based learning. Therefore, support from schools and training for teachers are important factors in optimising the inquiry method.